Free Throw Shooting Proficiency of Extracurricular Basketball Students at SMA Negeri 12 Luwu - Nurliani, Nurliani; Asyhari, Hasbi (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Objectives. This study aims to evaluate SMA Negeri 12 Luwu students' free throw shooting skills in their extracurricular basketball games. Materials and Methods. The nature of the study is quantitative and descriptive. The survey method utilized in this study to gather data includes the use of a free throw shooting abilities test or instrument. Twenty-five basketball players from SMA Negeri 12 Luwu made up the study's population. To guarantee that there were as many samples as there were students in the population—25—total sampling was the technique employed. The study's tool was a shooting skills test known as Free Throw. presenting the findings as percentages and applying quantitative descriptive data analysis. Results. Shooting prowess According to the percentages, students at SMA Negeri 12 Luwu who take part in free throw extracurricular activities are divided into three groups: "Very Good" (15 students), "Good" (36%), and "Poor" (4%). Conclusion. The results of the analysis show that during basketball games, the majority of SMA Negeri 12 Luwu extracurricular students' free throw shooting performance falls into the Very Good level.